T Cell Costimulatory Molecules in Anti-Viral Immunity: Potential Role in Immunotherapeutic Vaccines - Tania H Watts; Edward M Bertram; Jacob Bukczynski; Tao Wen (Canadian Journal of Infectious Diseases)
T lymphocyte activation is required to eliminate or control intracellular viruses. The activation of T cells requires both an antigen specific signal, involving the recognition of a peptide/major histocompatibility protein complex by the T cell receptor, as well as additional costimulatory signals. In chronic viral diseases, T cell responses, although present, are unable to eliminate the infection. By providing antigens and costimulatory molecules together, investigators may be able to increase and broaden the immune response, resulting in better immunological control or even elimination of the infection. Recent progress in understanding the function of costimulatory molecules suggests that different costimulatory molecules are involved in initial immune responses than are involved in recall responses. These new developments have important implications for therapeutic vaccine design. In this review the authors discuss the function of T cell costimulatory molecules in immune system activation and their potential for enhancing the efficacy of therapeutic vaccines.